2020
DOI: 10.3390/ijms21186903
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fbp2, a Newly Discovered Constituent of Memory Formation Mechanisms, Is Regulated by Astrocyte–Neuron Crosstalk

Abstract: Fbp2 (muscle isozyme of fructose 1,6-bisphosphatase) is a glyconeogenesis-regulating enzyme and a multifunctional protein indispensable for long-term potentiation (LTP) formation in the hippocampus. Here, we present evidence that expression of Fbp2 in murine hippocampal cell cultures is regulated by crosstalk between neurons and astrocytes. Co-culturing of the two cell types results in a decrease in Fbp2 expression in astrocytes, and its simultaneous increase in neurons, as compared to monocultures. These chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Fbp2 is also the predominant form of the enzyme in neurons [ 2 ]. Aside from regulation of glycogen synthesis from carbohydrate precursors, Fbp2, as a moonlighting protein, is engaged in cell cycle-dependent events [ 1 ], activation of synaptic plasticity phenomena [ 2 ], and regulation of activity of transcriptional factors [ 3 , 4 , 5 , 6 ]. It has been demonstrated that Fbp2 protects mitochondria against stress conditions such as a high level of calcium and its consequences (mitochondrial swelling and decreased ATP synthesis) [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fbp2 is also the predominant form of the enzyme in neurons [ 2 ]. Aside from regulation of glycogen synthesis from carbohydrate precursors, Fbp2, as a moonlighting protein, is engaged in cell cycle-dependent events [ 1 ], activation of synaptic plasticity phenomena [ 2 ], and regulation of activity of transcriptional factors [ 3 , 4 , 5 , 6 ]. It has been demonstrated that Fbp2 protects mitochondria against stress conditions such as a high level of calcium and its consequences (mitochondrial swelling and decreased ATP synthesis) [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fbp2 may be translocated to the cell nucleus in a hormone-dependent manner [ 12 ] where it regulates transcriptional activities of c-Myc and Hif1α [ 3 , 4 , 5 , 6 ]. Recently, Fbp2 has been shown to regulate synaptic plasticity by influencing the induction and maintenance of early and late phases of long-term potentiation (LTP).…”
Section: Introductionmentioning
confidence: 99%